2009
DOI: 10.1002/jmri.21751
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of hepatic steatosis with MRI: The effects of accurate fat spectral modeling

Abstract: Purpose: To develop a chemical-shift-based imaging method for fat quantification that accounts for the complex spectrum of fat, and to compare this method with MR spectroscopy (MRS). Quantitative noninvasive biomarkers of hepatic steatosis are urgently needed for the diagnosis and management of nonalcoholic fatty liver disease (NAFLD). Materials and Methods:Hepatic steatosis was measured with "fat-fraction" images in 31 patients using a multiecho chemical-shift-based water-fat separation method at 1.5T. Fat-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
251
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(259 citation statements)
references
References 43 publications
6
251
1
1
Order By: Relevance
“…In fact, this technique underestimates the fat signal because it accounts only for the methylene component in the triglyceride molecules that account for most of body fat. In the studies that introduced more accurate fat spectral models Reeder et al 2009), the authors showed linear relationship between multi-and single peaks fat models using in vivo data and phantoms. Using simulations, it was also shown that a linear relation exists between actual fat signal and the estimated one using three-point Dixon technique (Azzabou et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this technique underestimates the fat signal because it accounts only for the methylene component in the triglyceride molecules that account for most of body fat. In the studies that introduced more accurate fat spectral models Reeder et al 2009), the authors showed linear relationship between multi-and single peaks fat models using in vivo data and phantoms. Using simulations, it was also shown that a linear relation exists between actual fat signal and the estimated one using three-point Dixon technique (Azzabou et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound (US) is widely used to detect HS, without exposing subjects to ionizing radiations. Indeed, more specific imaging techniques [19] are costly and not always useful in close follow-up. Tsushima et al [20] first identified the so-called liver-spleen axis in NAFLD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The IDEAL-IQ sequence takes T2* and field homogeneity variations into consideration for fat fraction calculations. The details of the IDEAL-IQ sequence have been described elsewhere (13). The parameters of the IDEAL-IQ sequence were TR, 12.9 ms; FOV, 35-40 cm; matrix, 224×160; 125-kHz bandwidth; and slice thickness, 5 mm.…”
Section: Abstract: • Liver • Magnetic Resonance Imaging • Iron Overlmentioning
confidence: 99%
“…Hemosiderosis, most commonly seen in thalassemia patients, leads to an increased R2* value in the liver, which directly correlates with hepatic iron concentration (7). Recent advances in quantitative magnetic resonance imaging (MRI) methods have allowed for the separate and combined evaluation of liver fat and iron content (8)(9)(10)(11)(12)(13). We used an investigative version of the chemical shift-based water-fat separation method, which addresses all known confounding factors, specifically those involving T1, T2*, spectral complexity of fat, noise bias, and eddy currents (14,15).…”
mentioning
confidence: 99%